Specific coping behaviours related to depression in adolescents with a divorced parent - Dianovinina, Ktut; Surjaningrum, Endang Retno; Wulandari, Primatia Yogi (Intelektual Pustaka Media Utama, 2023)
Parents’ divorce is one of the life events that elicit pressure in adolescents, to such an extent that parents’ divorce is a predictor of depressive disorder in adolescents. Coping strategy plays an important role in the relationship between pressure and depression. This research aimed to examine coping strategies (problem-focused, emotion-focused, and dysfunctional coping) and specific coping behaviours which affect adolescents with divorced parents’ depressive symptoms. Participants are 80 adolescents with divorced parents from several cities in Indonesia, aged between 13 to 19 years old (mean=16.6 years, SD=1.62 with 76% female and 24% male). Depressive symptoms were measured using the children’s depression inventory, and specific coping behaviour was measured with Brief-COPE or coping orientation to problems experienced. In this research, it was found that 38% of the adolescents had depression. On the multiple linear regression, only problem-focused coping and dysfunctional coping significantly affected depression and not emotion-focused coping. Furthermore, among 14 specific coping behaviours, only instrumental support and behaviour disengagement affect depressive symptoms. These findings indicate that intervention focused on increasing the utilization of problem-focused coping and reducing dysfunctional coping might be beneficial to minimize depressive symptoms in adolescents with divorced parents.